Impact of synergistic interfacial modification on the electrochemical performance of LiNi0.5Mn1.5O4 cathode materials - Qureshi, Z.A. (2024)
Developing sophisticated lithium-ion batteries with high energy and power density requires using high-voltage positive electrodes. Due to its three-dimensional lithium-ion diffusion and greater nominal operating voltage, spinel LiNi0.5Mn1.5O4 has emerged as one of lithium-ion batteries' most viable cathode materials. Electrolyte breakdown, Mn dissolution, and rapid cathode-electrolyte interface (CEI) degradation in lithium-ion cells are exacerbated by the high operating voltage of LNMO. Consequently, the long-term cycling of LNMO is hampered by such adverse side effects, making the commercialization of such a battery impractical. Here, we document the enhancement in the electrochemical performance of LNMO by surface modification utilizing a combination of Al2O3 coating and Graphene enveloping employing a facile wet synthesis technique. The presence of highly crystalline spherical secondary microspheres consisting of primary nanoparticles of disordered LiNi0.5Mn1.5O4, the surface modification with Al2O3, and the subsequent graphene wrapping were all confirmed by structural and surface analysis techniques. The fabricated cells containing the enhanced cathode material (LNMO-Al-GO) were cycled at a C/10 rate for 100 cycles in a voltage window of 3.5–4.9 V, providing a specific discharge capacity of 134.7 ± 3.8 mAhg−1. Delivering a capacity retention of 97.7 ± 3.9% compared to the unmodified LNMO sample (84.7 ± 5.3%). Ex-situ XRD, Electrochemical Impedance Spectroscopy (EIS), and Differential Scanning Calorimetry (DSC) investigations reveal that the alumina coating protects the cathode by acting as a hydrogen fluoride (H.F.) scavenger and minimizes unfavorable phase formations at the CEI, inhibiting Mn3+ dissolution and enhancing cyclability.